PERANAN FAKTOR TRANSKRIPSI Hath1 DALAM DIFERENSIASI KARSINOGENESIS KOLOREKTAL - Reno Budiman; M.Nurhalim Shahib; Chairul Ismael; Basrul Hanafi Bujung (Universitas Padjadjaran, 2012)
Colorectal cancer (CRC) is the third most common cancer in the world. Various genetic, experimental and epidemiologic studieshave shown that CRC is derived from complex interaction between hereditary sensitivity and environment. Homeostaticenvironment deregulation at the mucous layer of the colon is the earliest sign of carcinogenesis. Hath1, a basic helix-loop-helix transcription factor, is an important positive regulator in terminal cell differentiation. The potential role of Hath1 in CRC is not clear yet. To reveal the answer, it is deemed necessary to observe the role of Hath1 in the differentiation of CRC. A case control study on two groups of subject was performed. The first group consisted of CRC patients who underwent colonoscopy of surgery. The second group consisted of patients who underwent colonoscopy due to other than CRC conditions. Subjects's tissue underwent histopathology examination, and RTPCR test to measure the strength of Hath1 expression. There was a significant difference of Hath1 expression between the two groups. Hath1 was expressed with various strength on CRC group, however it was weakly expressed at control subjects. Hath1 was expressed stronger on late stage of the disease, and on moderate to poor differentiation. There was no significant difference between Hath1 expression on mucinous or non-mucinous types. Inconclusion, the study has shown the role of transcription factor Hath1 in the carcinogenesis of CRC. Hath1 was stronglyexpressed on late stage and poorly differentiated subjects. The examination of transcription factor Hath1 is a feasible biomolecular marker to describe the level of malignancy in the CRC.